Paralleizing AwSpPCA for robust facial recognition using CUDA - Zawad, Syed Amer (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.